Phyllanthus (Phyllanthus multiflorus Willd.) Fruit as Natural pH Indicator - Fuentes, Princess Lydia S; Legaspi, Jocelyn S; Albaladejo, Veronica E (International Journal of Advanced Engineering Research and Science, 2021)
A substance property as an acid or a base is determined in terms of quantity of pH. It makes use of various tools ranging from simple litmus paper to the sophisticated benchtop pH meter. Natural indicators on the other hand are utilized as an alternative to synthetic acid-base indicators. This paper relates to the preparation of natural indicator from Phyllanthus fruit containing anthocyanin, and the establishment of its effectiveness. The experimental method of this study is composed of the preparation of raw materials, standardization of solutions, calibration, testing for effectiveness, and development of a color chart. The developed pH indicator consists of Phyllanthus fruit, water, and ethanol. The process of producing the pH indicator comprises of the following steps: collecting; washing; weighing; crushing; mixing with water; boiling the mixture; filtering; cooling down; mixing with ethanol; soaking; and drying. The calibration of the indicator involves different solutions with pH 0 to 14 to come up with a color chart. This serves as a reference in the effectiveness test. Treatment 2 of the indicator produced a distinctive color that is comparable to the existing pH measurement tool. This finding indicates that the pH indicator from Phyllanthus fruit consisting of a 1:1 ratio of fruit to water, and a 1:1.5 ratio of the mixture to ethanol can be a cheaper alternative tool in measuring pH that can be used in laboratory testing, as instructional material, and in the household.